2018
DOI: 10.1111/ssqu.12547
|View full text |Cite
|
Sign up to set email alerts
|

“I Just Don't Think She Has a Presidential Look”: Sexism and Vote Choice in the 2016 Election*

Abstract: Objectives. This article examines the effect of both modern and traditional sexism on vote choice in the 2016 presidential election, and posits that they played a major role in explaining Hillary Clinton's defeat to Donald Trump. Methods. Data from the 2016 American National Election Study are analyzed using a logistic regression model. Results. Both modern and traditional sexism exerted a statistically significant effect on presidential vote choice in 2016. Indeed, its effect rivaled that of racial resentment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
1
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 40 publications
0
33
1
1
Order By: Relevance
“…With regard to the 2016 election, several studies have found that greater endorsement of sexist beliefs about women was related to voting for Trump (e.g., [25,26]). In particular, Bock et al [8] found that undergraduate students who endorsed greater hostile sexism toward women (post-election) were more likely to have voted for Trump instead of Clinton.…”
Section: Sexismmentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to the 2016 election, several studies have found that greater endorsement of sexist beliefs about women was related to voting for Trump (e.g., [25,26]). In particular, Bock et al [8] found that undergraduate students who endorsed greater hostile sexism toward women (post-election) were more likely to have voted for Trump instead of Clinton.…”
Section: Sexismmentioning
confidence: 99%
“…With regard to the 2016 election, a few studies have found that greater endorsement of racism or less concern about racism were related to voting for Trump instead of Clinton (e.g., [26,9]). Given suggestions about the status threat of some White Americans and Trump's campaign rhetoric, Modern Racism may have contributed to the results of the 2016 presidential election.…”
Section: Racismmentioning
confidence: 99%
See 1 more Smart Citation
“…It is accurate to state that considerable research has found that sexism negatively influenced Clinton's 2016 presidential campaign (Cassese and Holman 2019;Knuckey 2019;Monteith and Hildebrand 2019;Schaffner, MacWilliams, and Nteta 2018;Valentino, Wayne, and Oceno 2018). However, these findings are not without critique; Zigerell (2019) claimed that current measurements of sexism measure bias only toward women and do not account for anti-man bias.…”
mentioning
confidence: 99%
“…Or consider research on gender attitudes and support for Donald Trump in Bracic, Israel-Trummel, and Shortle (2018); Cassese and Barnes (2018); Cassese and Holman (2019); Frasure-Yokley (2018); Knuckey (2018); Schaffner, MacWilliams, and Nteta (2018); Setzler and Yanus (2018); and Valentino, Wayne, and Oceno (2018). Each article had “sexism” in the title or abstract, but the gender-attitudes items did not measure attitudes disfavoring men.…”
mentioning
confidence: 99%